2006
DOI: 10.1097/01.prs.0000222555.84962.86
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-Based Appraisal of the Use of Hyperbaric Oxygen on Flaps and Grafts

Abstract: Hyperbaric oxygen has been advocated, both as an adjunctive or primary form of treatment, for a variety of disorders, including gas gangrene, osteoradionecrosis, and carbon monoxide poisoning. It has also been used to improve ischemic wounds before skin grafting and to support ischemic flaps. In this review, we analyze the available literature that investigates the use of hyperbaric oxygen for composite grafts, skin grafts, random flaps, distant flaps, and free flaps. An appraisal of the level of evidence for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 54 publications
1
39
0
1
Order By: Relevance
“…The fibroblasts are the major producers of collagen in the repairing process. Hypoxia affects fibroblast activity by decreasing IGF-1 production, increasing TGF-β production, and increasing procollagen mRNA levels [19,20]. Many substances in the literature have been investigated for their ability to eliminate tissue ischemia and ischemic consequences such as low oxygenation and perfusion deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The fibroblasts are the major producers of collagen in the repairing process. Hypoxia affects fibroblast activity by decreasing IGF-1 production, increasing TGF-β production, and increasing procollagen mRNA levels [19,20]. Many substances in the literature have been investigated for their ability to eliminate tissue ischemia and ischemic consequences such as low oxygenation and perfusion deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…24 An extreme therapeutic example is hyperbaric oxygenation (HBO), which typically uses 100% oxygen at 3 atmospheres and has been applied for various purposes, including promoting wound healing for grafting or supporting flap survival. 5,6 HBO, however, can be used clinically only for 60–90 minutes per day due to its pulmonary toxicity. 7 The systemic influences of the strong toxicity and the repeated rebounding effects remain to be determined, and the therapeutic benefits of HBO remain controversial, limiting expanded use.…”
mentioning
confidence: 99%
“…Factors that limit wide acceptance of HBO as a part of the standard treatment of chronic wounds include inconsistent results in the clinical setting, flaws in the design of some studies and an insufficient number of clinical trials [83][84][85][86][87][88]. However, various studies have shown HBO to be an effective adjunctive therapy for chronic diabetic ulcers [89][90][91][92].…”
Section: Hyperbaric Oxygen Therapy In the Clinical Settingmentioning
confidence: 99%